UVB exposure of a humanized skin model reveals unexpected dynamic of keratinocyte proliferation and Wnt inhibitor balancing. (10th December 2017) - Michalczyk, Teresa; Biedermann, Thomas; Böttcher‐Haberzeth, Sophie; Klar, Agnes S.; Meuli, Martin; Reichmann, Ernst
Abstract: We developed human dermo‐epidermal skin substitutes that are presently applied in phase I and II clinical trials. Here, we used these very same skin equivalents containing melanocytes, named MelSkin, as an experimental skin model. We investigated the effects of ultraviolet B (UVB) irradiation on the skin grafts transplanted on immune‐compromised rats. The irradiation induces a strong wound healing response going along with massive proliferation of basal keratinocytes, basically quiescent under nonirradiated, homeostatic conditions. As a consequence of UVB irradiation, the initially clearly defined basal keratinocyte (mono)layer expands into about 3 layers of keratinocytes, all of which still express the basal keratinocyte marker keratin 15. In contrast, epidermal melanocytes remain quiescent under these circumstances. Moreover, the Wnt inhibitors Dickkopf 3 and Wif1 are downregulated upon UVB irradiation in basal keratinocytes, whereas melanocytes continue to express Wnt inhibitors. These findings suggest that there is (a) a suprabasal population, proliferating in the homeostatic state, hence maintaining the integrity of the epidermis, and (b) a basal, usually quiescent keratinocyte population that is induced to massively proliferate upon irradiation. Importantly, the finding that MelSkin responds in a physiological fashion to UVB is of paramount importance in light of the planned clinical application.